Comparison of understanding of mathematical and mathematics history texts - Gudelytė, Laura; Kastickaitė, Joana; Krylovas, Aleksandras; Laukevičius, Tadas (Lietuvos matematikos rinkinys, 2010)
The article compares results of testing how students in the field of social sciences understand the text in mathematics and math history. During the experiment 128 second-year students in the Bachelor’s studies in the Public Administration Programme at Mykolas Romeris University were surveyed. They used given texts in mathematics and math history during the lecture. To compare their understanding, closed-end tests were used. The results of testing have been analysed using statistical methods.